2005
DOI: 10.1080/00015458.2005.11679740
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Motility Factor Receptor Expression Implies an Unfavourable Prognosis in Resected Stage I Pulmonary Adenocarcinomas

Abstract: AMFR expression predicts an unfavourable surgical outcome in patients with stage I pulmonary adenocarcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…In a study of hepatocellular cancer cells, Wang et al reported that the patients with high expression of AMFR had higher recurrence or metastasis and shorter survival periods than those with low expression of AMFR (7). Kaynak et al also put forward that AMFR expression was a possible prognostic factor for survival and had a correlation with clinicopathological features and the 3-year survival rates of AMFR-positive and AMFR-negative patients were 47.3% and 84.6%, respectively, in stage I pulmonary adenocarcinoma (9). In this study, we examined that AMFR and its downstream target ROCK-2 were expressed in two ESCC cell lines at both mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In a study of hepatocellular cancer cells, Wang et al reported that the patients with high expression of AMFR had higher recurrence or metastasis and shorter survival periods than those with low expression of AMFR (7). Kaynak et al also put forward that AMFR expression was a possible prognostic factor for survival and had a correlation with clinicopathological features and the 3-year survival rates of AMFR-positive and AMFR-negative patients were 47.3% and 84.6%, respectively, in stage I pulmonary adenocarcinoma (9). In this study, we examined that AMFR and its downstream target ROCK-2 were expressed in two ESCC cell lines at both mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 88%
“…Aberrant expression of AMFR has been observed in many cancers and its expression level is correlated with the metastasis ability of cancer cells (7)(8)(9)(10). In a study of hepatocellular cancer cells, Wang et al reported that the patients with high expression of AMFR had higher recurrence or metastasis and shorter survival periods than those with low expression of AMFR (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kho et al affirmed that in human breast carcinoma the interaction of AMF with HER2 triggers HER2 phosphorylation and metalloprotease-mediated ectodomain shedding, activating PI3K and MAPK signaling and hinders trastuzumab effect (Kho et al, 2013 ). Several studies reported the overexpression of AMFR in different types of human cancer, including esophageal carcinoma, breast carcinoma, pulmonary cancer and melanoma (Tímár et al, 2002 ; Kaynak et al, 2005 ; Kojic et al, 2007 ; Wang et al, 2010a ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were seen in other studies also, where high expression of AMFR was found to be implicated in mediating invasion of lung and oral squamous cell carcinomas and promoting their metastatic capabilities (Niinaka et al, 2002 ; Takanami et al, 2002 ; Takanami and Takeuchi, 2003 ). A positive association between AMFR and metastasis was observed in melanoma cells also (Tímár et al, 2002 ); whereas, in pulmonary adenocarcinoma patients, AMFR positive subjects have shown a lower post-surgery survival rate, as compared to those having no significant AMFR expression (Kaynak et al, 2005 ).…”
Section: The Multiple Roles Of Gp78 In Cellular Proliferation: Novel mentioning
confidence: 99%